The Effectiveness of Allium cepa L Compress on Body Temperature of Fever Infants after DPT Immunization (Diphtheria Pertussis Tetanus) at Posyandu Kenanga Kertajaya Village, Purwakarta Regency, Indonesia - Nova Rati Lova; Rica Rianjani (Archives of The Medicine and Case Reports, 2023)
Fever in infants after DPT immunization can cause concern for parents and health care providers. One alternative that is widely used in relieving fever in infants is by applying compresses using natural ingredients. One of the natural ingredients used in compresses is Allium cepa L, or better known as shallots. This study aimed to evaluate the effectiveness of compressed Allium cepa L on the body temperature of infants with fever after DPT immunization at Posyandu Kenanga Kertajaya Village, Purwakarta Regency, Indonesia. This study was an experimental study, where as many as 30 research subjects participated in this study. The research subjects were grouped into the intervention group and the control group. Data analysis was carried out using SPSS univariate and bivariate. Giving compresses Allium cepa L statistically effective in reducing the temperature of research subjects by 0.6°C and statistically significant, p<0.05. Compress Allium cepa L effective in reducing body temperature in infants with fever after DPT immunization at Posyandu Kenanga Kertajaya Village, Purwakarta Regency, Indonesia.